Low-coherence optical fibre speckle interferometry - Balboa, Itziar; Ford, Helen D.; Tatam, Ralph P. (IOP Publishing, 2006)
This paper describes the development of optical fibre low-coherence speckle interferometers capable of three-dimensional surface profiling with a resolution of 10–20 µm and a depth range of typically tens of centimetres. The technique is absolute, enabling the measurement of steps and through holes. The inclusion of optical fibres enables compact, flexible configurations to be realized, alleviating the experimental difficulties encountered with bulk interferometers, particularly when using long path lengths for measurements on large test objects. Sources including light-emitting and superluminescent diodes and multimode laser diodes are compared, and the use of a multimode laser diode source in pulsed mode is shown to improve depth resolution. Fibre-based systems using both single mode and polarization-maintaining fibre are described, and the results of experimental measurements on a stepped test object, a tilted plate and a coin are presented. A depth resolution of ±20 µm is obtained for the standard fibre system and ±14 µm for the system based on polarization-maintaining fibre.
Keywords: low-coherence; speckle interferometry; profilometry; shape measurement